ODAMLARDA TISH EMALINING QATTIQLIGI VA UNI MUSTAHKAMLASH USULLARI - Bakirova Feruza Xasanboy qizi, (TADQIQOTLAR, 2026)
Annotation: Enamel is the hardest tissue in the human body and plays a critical role  in  protecting  teeth  from  mechanical  damage,  chemical  erosion,  and  bacterial infections. However, enamel can demineralize due to acidic foods, poor oral hygiene, and systemic conditions, leading to increased susceptibility to caries and sensitivity. Recent  studies  focus  on  strengthening  enamel  through  remineralization techniques, such  as  fluoride  application,  casein  phosphopeptide-amorphous  calcium  phosphate (CPP-ACP) treatments, and the use of bioactive materials in dental care products [1, 2]. Additionally, diet modification, oral hygiene improvement, and preventive dental therapies  have  shown  significant  effects  on  maintaining  enamel  hardness  [3,  4]. Understanding  these  methods  contributes  to  the  prevention  of  dental  diseases  and promotes long-term oral health.